The Eppo/Olaf Compendium of National Procedures - Hauck, Pierre (Logos Verlag Berlin, 2025)
Poland does not participate in the EPPO mechanism, but cooperates with OLAF. Therefore, this Polish EPPO/OLAF volume, introduced by Dominika Czerniak, discusses the specific attitude of Polish legislation towards the PIF acquis sector, Title V of the TFEU, the importance of Art. 587 (European Investigation Order) of the Polish Code of Criminal Procedure and the newly inserted Art. 615a. It also contains an analysis and compilation of the EU and Polish legislation on EU fraud offenses. These relevant laws are dealt with in the first chapter of this volume. The Anti-Fraud Office (OLAF) and its national partners carry out investigative missions, which are the subject of the second part of the book. Dr. Dominika Czerniak acted as the publication’s national expert. While written in English, the volume includes footnotes that reproduce the original Polish legislation in the local language. Easily navigable with the help of visual symbols, it is designed as a quick reference tool for academics, students, practitioners and other interested readers.